INFLUENCE OF THE AESTHETIC STANDARDS IN BODY IMAGE OF YOUNG WOMENS GENDER: A STUDY WITH TEACHERS AND STUDENTS IN SCHOOL PHYSICAL EDUCATION (Fiep Bulletin - online, 2011)
The presented article is the result of initial studies in the doctoral program. It shows a series of questions and reflections on the imposition of aesthetic standards for the body and the consequences in the formation of the body image of adolescent females. It presents the scientific community's concerns with the increase of people's dissatisfaction with their bodies and the pursuit at all costs to be within the standards imposed culturally. The study will be conducted with teachers and young students and will have the physical education classes as the research environment. We present a theoretical framework, objectives and methodology to be applied.
Keywords: Physical Education; Interactive processes